Firm-Level Data and Monetary Policy : The Case of a Middle Income Country - Bounader, Lahcen (IMF Working Papers; Working Paper ;, 2019)
We test the existence of the balance sheet channel of monetary policy in a middle-income country. Firm-level data scarcity and quality, in such a context, make the identification of this channel a steep challenge. To circumvent this challenge, we use panel instrumental variables estimation with measurement error to analyze the financial statements of 58 500 Moroccan firms over the period 2010-2016. Our analysis confirms the existence of this channel. It shows that monetary policy has a significant impact on small and medium enterprises' access to banks' financing, and that firm-specific variables are key determinants of firms' financing decisions.